2012
DOI: 10.3109/08958378.2012.668229
|View full text |Cite
|
Sign up to set email alerts
|

Manufactured and airborne nanoparticle cardiopulmonary interactions: a review of mechanisms and the possible contribution of mast cells

Abstract: Human inhalation exposures to manufactured nanoparticles (NP) and airborne ultrafine particles (UFP) continues to increase in both occupational and environmental settings. UFP exposures have been associated with increased cardiovascular mortality and morbidity, while ongoing research supports adverse systemic and cardiovascular health effects after NP exposures. Adverse cardiovascular health effects include alterations in heart rate variability, hypertension, thrombosis, arrhythmias, increased myocardial infar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 184 publications
2
35
0
Order By: Relevance
“…Even though mast cells appear to be central in the pathogenesis following NP exposure little research has been done assessing the direct interaction of NPs with mast cells. While mast cells are well-known to be involved in allergic conditions, it is currently unclear if NPs have the capacity to induce and/or promote an allergic disease state (Podila and Brown, 2013; Shannahan and Brown, 2014; Shannahan et al, 2012). One study reported that AgNPs can induce mast degranulation in the RBL-2H3 rat basophilic cell line, however, the study was focused on real-time live cell imaging of the degranulation process but not the influence of physicochemical properties of AgNPs (Yang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Even though mast cells appear to be central in the pathogenesis following NP exposure little research has been done assessing the direct interaction of NPs with mast cells. While mast cells are well-known to be involved in allergic conditions, it is currently unclear if NPs have the capacity to induce and/or promote an allergic disease state (Podila and Brown, 2013; Shannahan and Brown, 2014; Shannahan et al, 2012). One study reported that AgNPs can induce mast degranulation in the RBL-2H3 rat basophilic cell line, however, the study was focused on real-time live cell imaging of the degranulation process but not the influence of physicochemical properties of AgNPs (Yang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] It has been confirmed that NPs can systemically translocate to the circulation from the lung. 12 Subsequently, translocated particles could mediate cardiovascular effects through direct interaction with vasculature, blood, and the heart. The cardiovascular toxicity of NPs has gradually drawn attention.…”
Section: Guo Et Almentioning
confidence: 99%
“…In our lab, we have demonstrated that exposure to MWCNTs by oropharyngeal aspiration in C57BL/6 mice induced a significant increase in production of IL-33 (Wang et al, 2011). We speculated that the increased levels of IL-33, released from damaged lung epithelial cells, subsequently activated mast cells resulting in adverse pulmonary and cardiovascular responses in mice (Shannahan et al, 2012). These MWCNT induced toxicities appear to be mast cell dependent as MWCNT failed to induce these toxicities in mast cell-deficient mice.…”
Section: Immunotoxicity Of Enm Through Different Immune Cellsmentioning
confidence: 99%